2013
DOI: 10.22452/adum.vol20no2.3
|View full text |Cite
|
Sign up to set email alerts
|

Developing a caries risk assessment model for patients attending University Malaya dental clinic

Abstract: Aim: In response to the introduction of an integrated dental education program at University of Malaya (UM) in 2011, a study was conducted to develop a caries risk assessment model (CRA) for use in non-surgical caries management for Year 3 and 4 students of the new integrated program. Methods: The CRA model was based on risk indicators used by dental students in the Preventive Dental Clinic (PDC). Patients aged 15 years and above who attended the PDC for the first time in year 2009 and 2010 were used as study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…caries activity was significantly less in the older population. This is in congruence with the research reported by Asma et al and Qasim et al regarding age and caries cavity 24,25 A study by Alves et al reported that eruption stage was significantly associated with occlusal caries activity 30 .The author also reported that partially erupted molar as compared to fully erupted were five times more likely to have active caries but only second molars were evaluated 30 . Our study also reported similar results and found a significant association between eruption status of first molar with caries activity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…caries activity was significantly less in the older population. This is in congruence with the research reported by Asma et al and Qasim et al regarding age and caries cavity 24,25 A study by Alves et al reported that eruption stage was significantly associated with occlusal caries activity 30 .The author also reported that partially erupted molar as compared to fully erupted were five times more likely to have active caries but only second molars were evaluated 30 . Our study also reported similar results and found a significant association between eruption status of first molar with caries activity.…”
Section: Discussionsupporting
confidence: 86%
“…A higher Oratest time was recorded for females in our study, but the result was not statistically significant. Multiple other studies have also reported similar results [23][24][25] . However, higher Oratest time in males as compared to females was reported by Ambati et al 13 but the results were not significant.…”
Section: Discussionsupporting
confidence: 73%